Investigation of the Isochrone Concept for Predicting Relaxation of Geogrids. Issue 2 (1st January 2000) - Dechasakulsom, M.; Leshchinsky, D.; Kaliakin, V.N.
Abstract : Due to the perceived complexity of relaxation tests, the relaxation response of geosynthetics has, in the past, been predicted from isochronous curves generated from creep tests. However, the validity of such an approach has not been extensively investigated. Using experimental data from in-isolation creep and relaxation tests performed on eleven different geogrids, the validity and limitations of using creep isochronous curves to predict relaxation response of geogrids has been investigated. Acceptable agreement between predicted and experimental relaxation responses was rather limited, being observed for specimens tested at low initial load levels and for materials exhibiting relatively large creep strains. With minor exceptions, the experimentally measured force relaxation was under-predicted by using the isochrone approach. Nonetheless, it appears that for the geogrids tested, overall accurate relaxation response cannot be predicted from isochronous curves constructed using creep data.